Massive star cluster formation: I. High star formation efficiency while resolving feedback of individual stars - Polak, Brooke; Low, Mordecai-Mark Mac; Klessen, Ralf S.; Teh, Jia Wei; Cournoyer-Cloutier, Claude; Andersson, Eric P.; Appel, Sabrina M.; Tran, Aaron; Lewis, Sean C.; Wilhelm, Maite J. C.; Zwart, Simon Portegies; Glover, Simon; et al. (Astronomy and astrophysics, 2024)
The mode of star formation that results in the formation of globular clusters and young massive clusters is difficult to constrain through observations. We present models of massive star cluster formation using the TORCH framework, which uses the Astrophysical MUltipurpose Software Environment (AMUSE) to couple distinct multi-physics codes that handle star formation, stellar evolution and dynamics, radiative transfer, and magnetohydrodynamics. We upgraded TORCH by implementing the N-body code PETAR, thereby enabling TORCH to handle massive clusters forming from 10 6 M⊙ clouds with ≥10 5 individual stars. We present results from TORCH simulations of star clusters forming from 10 4, 10 5, and 10 6 M⊙ turbulent spherical gas clouds (named M4, M5, M6) of radius R = 11.7 pc. We find that star formation is highly efficient and becomes more so at a higher cloud mass and surface density. For M4, M5, and M6 with initial surface densities 2.325 × 10 1,2,3 M⊙ pc −2, after a free-fall time of t ff = 6.7,2.1,0.67 Myr, we find that ∼30%, 40%, and 60% of the cloud mass has formed into stars, respectively. The end of simulation-integrated star formation efficiencies for M4, M5, and M6 are ϵ⋆ = M⋆/M cloud = 36%, 65%, and 85%. Observations of nearby clusters similar in mass and size to M4 have instantaneous star formation efficiencies of ϵ inst ≤ 30%, which is slightly lower than the integrated star formation efficiency of M4. The M5 and M6 models represent a different regime of cluster formation that is more appropriate for the conditions in starburst galaxies and gas-rich galaxies at high redshift, and that leads to a significantly higher efficiency of star formation. We argue that young massive clusters build up through short efficient bursts of star formation in regions that are sufficiently dense (Σ ≥ 10 2 M⊙ pc −2) and massive (M cloud ≥ 10 5 M⊙). In such environments, stellar feedback from winds and radiation is not strong enough to counteract the gravity from gas and stars until a majority of the gas has formed into stars.